Sharia Perspective: The Urgency of Islamic Economic, Banking and Finance (IEBF) Reform in realizing the Sustainable Development Goals (SDGs) through Knowledge Integration (IoK) Approach - Ahmad Munir Hamid (Universitas Islam Darul 'ulum Lamongan, 2024)
This research explores the pressing need for reform within the realm of Islamic Economic, Banking, and Finance (IEBF) from a Sharia perspective, with a particular focus on its crucial role in advancing the Sustainable Development Goals (SDGs). What sets this study apart is its innovative approach, emphasizing Knowledge Integration (IoK) as a powerful tool for achieving this reform. Through a comprehensive examination of IoK's methodological principles, including permissibility, acceptability, authenticity, and contextual adaptability, this research seeks to uncover novel ways to align IEBF practices with the principles of Sharia and the SDGs. The study emphasizes the importance of policymakers actively supporting both academic and industry efforts to incorporate IoK principles into IEBF practices. By doing so, it aims to validate the effectiveness of these principles in achieving the SDGs and fulfilling the broader maqasid. Moreover, the research highlights the potential for substantial cost savings when extracting valuable insights from the legacy writings of IoK and IEBF to guide contemporary IEBF practices. In summary, this study sheds light on the unique novelty of adopting the Knowledge Integration (IoK) approach to reform IEBF in alignment with Sharia principles and the SDGs. By doing so, it not only strengthens the scientific foundations of IEBF but also paves the way for its broader and more impactful contribution to sustainable development on a global scale. Keywords: Integration of Knowledge, (IEBF), Sharia, and SDGs.